Case study on Singapore Changi Airport - Ang, Lay Tin (2008)
This project examines the development of Singapore Changi Airport, the change from Department of Civil Aviation to Civil Aviation Authority of Sinagpore, the financing of the airport and the comparison of financial and non-financial performance of Singapore Changi Airport over the years 1981-2001.